Great Rivers of the World (Washington, D. C. National Geographic Society., 1984)
"Each spread in this book, which includes a goregeous gatefold page, offers a colorful map packed with drawings, figures, and facts. Cities that border the rivers are highlighted, as are distinct flora and fauna, significant natural and human-made features, and fascinating historical details. A "biography" of each river describes where it flows, and its importance to the communities it passes through. Special attention is given to the ecological health of the rivers--those that are thriving and those in danger of losing their valuable habitats. Along the way, young readers will come to understand the enormous impact that rivers have on our lives, while learning valuable information in a way that will spark their curiosity and imagination."
Includes index.
English text.